2009
DOI: 10.1111/j.1475-097x.2008.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between plasma adrenomedullin concentration and systolic time intervals during static handgrip in patients with heart failure

Abstract: Our previous study showed elevation of plasma adrenomedullin (ADM) during static handgrip in patients with heart failure (HF). It is hypothesized that ADM increases with left ventricle dysfunction during handgrip and thus plays a compensatory role. In the present study pre-ejection period (PEP) and left ventricular ejection time (LVET) were used to assess cardiac performance in 24 male HF patients (II/III class NYHA) during two 3-min bouts of handgrip at 30% of maximal voluntary contraction (MVC) performed alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…Our findings also confirm the observations of Krzeminski et al (2009) that during increased inotropic states, variations in systolic time intervals uncorrected for heart rate reflect systolic changes well. That is, in situations of increased inotropy, such as during epinephrine infusion, systolic time intervals corrected for heart rate may mask the associated inotropic effect (Krzeminski et al 2009). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also confirm the observations of Krzeminski et al (2009) that during increased inotropic states, variations in systolic time intervals uncorrected for heart rate reflect systolic changes well. That is, in situations of increased inotropy, such as during epinephrine infusion, systolic time intervals corrected for heart rate may mask the associated inotropic effect (Krzeminski et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…For detailed analysis of systolic time intervals see (Carliner et al 1974). Finally, in situations of increased inotropy, such as during epinephrine infusion, systolic time intervals corrected for heart rate may mask the associated inotropic effect (see Krzeminski et al 2009). To confirm this observation, therefore, we present both the absolute systolic time intervals (LVET, PEP) and heart rate changes based indices (LVETi, PEPi).…”
Section: Methodsmentioning
confidence: 99%
“…Inverse relationships between static handgrip-induced changes in plasma ADM and those in PEP, PEP/LVET ratio, peak velocity and mean acceleration of the blood flow in the ascending aorta, and mean velocity of circumferential fiber shortening might be at least partly associated with inotropic action of ADM on the heart (Krzeminski et al, 2009, 2012; Krzeminski and Pawlowska-Jenerowicz, 2012). It should be noted that the PEP/LVET ratio has been proposed as a sensitive inverse index of left ventricular myocardial performance (Lewis et al, 1977; Martin et al, 1971; Weissler et al, 1969, 1972, 1980).…”
Section: Adrenomedullin and Static Exercisementioning
confidence: 99%
“…On the other hand, we have recently demonstrated that static handgrip caused also an increase in the plasma adrenomedullin (ADM), which is a potent vasorelaxant probably involved in the fine blood pressure control counteracting the effect of vasoconstrictors. The increase in plasma ADM level was found in older healthy subjects and patients with heart failure (Krzeminski et al 2002, 2006, 2009). …”
Section: Introductionmentioning
confidence: 98%
“…Since our previous study performed in older healthy men and in patients with heart failure (Krzeminski et al 2002, 2006, 2009) showed interrelationships between changes in plasma ADM, catecholamine and cardiovascular responses to handgrip, it seemed of interest to extend these data to healthy young persons. Our hypothesis is that in healthy older subjects, the contribution of vasoactive hormones to cardiovascular response to static handgrip is greater than in young men.…”
Section: Introductionmentioning
confidence: 99%